KENALI DAN CEGAH KELAHIRAN BERAT BAYI LAHIR RENDAH SEJAK DINI - Ratnasari, Febi; Atsari, Sarah Citra; Sumarni, Deswyta Try; Andiawati, Rosa; Pratiwi, Riska; Hulu, Titusman; Fitriana, Eva; Adawiah, Siti Robiatul; Nurhayati, Siti; Litaferina, Vindy; Sugiyanti, Winda (Nusantara Hasana Journal, 2022)
Low birth weight babies can be recognized and prevented early. Objective to find out what precautions can be taken to prevent the birth of low birth weight babies. Method: health education. From the results of health education, it was found that fertile women know how to prevent low birth weight babies.